Kesenjangan Digital dan Dampaknya terhadap Pertumbuhan Ekonomi di Afrika Selatan - Remeiliza Fitri (Economic Reviews Journal, 2024)
The global digital divide refers to the disparity in access to and utilization of information and communication technologies (ICTs) between countries and regions, which is recognized as a critical issue in economic and social development. This divide encompasses not only access to technological infrastructure but also inequalities in internet usage for various activities, which can impact a country's economic growth. This study focuses on the relationship between the digital divide and regional economic growth, using South Africa as a case study. Despite significant progress in technological infrastructure development, particularly in the digital sector, South Africa's economy has shown stagnation or even decline. This contrasts with much research suggesting that better digital access tends to drive economic growth. Therefore, this study aims to explore other factors that may influence the relationship between the digital divide and economic growth, such as government policies, economic structure, and other social factors. By understanding these dynamics, it is hoped that new insights can be gained into the role of the digital divide in regional economic development, particularly in developing countries like South Africa.